First Report of Fusarium solani and Fusarium oxysporum Causing Basal Stem Rot on Celery in China - Wang, Ruoyu; Xie, Xiaofan; Yang, Liu; Chen, Gaofeng; Zhou, Qin; Wang, Yun; Zhang, Yubao (Plant disease, 2023)
Celery (Apium graveolens L.) is an economically important vegetable crop in China. In recent years, celery has been widely planted in Yuzhong county, Gansu province. From 11 April to 24 May, 2019-2021, basal stem rot of celery was observed with incidences up to 15% in the Yuzhong region (35°49'N, 104°16'E, 1865 m a.s.l.), which caused serious economic losses to local farmers. Typical symptoms of the disease included wilting and darkening of the basal stem, leading to plant death. To identify the cause of the disease, small pieces (5mm×5mm) of the margin of asymptomatic and rotting basal stem tissues were sterilized with 70% ethanol for 30 s and 3% NaClO for 5 min, then placed on potato dextrose agar (PDA) plates, and incubated at 25℃ (Zhao et al. 2021). Twenty-seven single-conidium isolates with morphological characteristics similar to Fusarium spp. were obtained (Ma et al. 2022), which displayed two kinds of colony morphology. On PDA, seven isolates developed white, fluffy aerial mycelium and twenty isolates developed light pink abundant aerial mycelium. Isolate F5 and F55 from each distinct morphological group were cultured on PDA and synthetic low nutrient agar (SNA) for pathogenicity tests, morphological and molecular identification. The macroconidia (18.3 to 29.6 × 3.6 to 5.3 μm, n=50) with 1 to 2 septa and microconidia (7.5 to 11.6 × 2.6 to 3.5 μm, n=50) with 0 to 1 septum were observed in F5. For F55, the size of macroconidia was 14.2 to 19.5 × 3.3 to 4.2 μm (n = 50) with 1 to 2 septa; Microconidia were mostly 0 to 1 septum and measured 7.3 to 12.8 × 2.2 to 4.2 μm (n = 50). To confirm the identity of the isolates, the internal transcribed spacer region (ITS) and the translation elongation factor-1 alpha (TEF-1α) gene were amplified using primers ITS1/ITS4 and EF-1/EF-2 (Uwaremwe et al. 2020), respectively. The sequence similarities of isolate F5 (GenBank No. OL616048 and OP186480) and F55 (GenBank No. OL616049 and OP186481) with the corresponding sequences of F. solani (MT447508 and MN650097) and F. oxysporum (MG461555 and OQ632904) ranged from 99.22% to 100.00%, with matching base pairs of 531/532, 416/416, 511/515 and 394/395, respectively. The voucher samples were deposited in the sample center of Northwest Institute of Ecological Environment and Resources, Chinese Academy of Sciences. Morphological and molecular results confirmed the species of F5 and F55 as F. solani and F. oxysporum, respectively. A pathogenicity test was conducted under greenhouse conditions (19-31°C, avg. 26°C). Conidial suspension (105 spores/mL) of isolates F5 and F55 were poured onto the basal stems of healthy celery seedlings at the age of 1 month and mock-inoculated control treatments with sterile water. Ten plants were inoculated for each treatment. After 21 days, all plants inoculated with both fungal isolates developed symptoms similar to those observed in the field, whereas the mock-inoculated plants remained healthy. The pathogen was successfully reisolated from the inoculated symptomatic plants onto PDA medium and had morphology as described above, confirming Koch's postulates. F. solani and F. oxysporum have been reported to infect many plant species, including carrot (Zhang et al. 2014) and Angelica sinensis (Liu et al. 2022). To our knowledge, this is the first report that F. solani and F. oxysporum cause basal stem rot on celery in China. The identification of pathogens of the observed basal stem rot on celery provides a clear target for the prevention and management of this disease.